Mixed Chloro Derivatives of Vanadium Dialkyl and Alkylene Dithiophosphates - El-Khaldy, A.A.S. (Asian Journal of Chemistry, 2010)
Mixed chloro vanadium derivatives of dialkyl and alkylene dithiophosphates of general formula CIV[S2P(OR)2]2 where R = Prn and Ph and cyclic where G = — CH2— CMe2— CH2—, CMe2CMe2— and —CH2CEt2CH2— have been synthesized by the reaction of vanadium trichloride with dithiophosphoric acids in 1 : 1 and 1 : 2 molar ratio in suitable organic solvents. These new derivatives have been characterized by elemental analysis. molecular weight determinations as well as spectroscopic (IR, 1H, 13C and 31P NMR) studies. On the basis of these data chelated structures with bidentate dialkyl and alkylene dithiophosphate groups have been proposed for these monomeric derivatives.